Exploring the linkage between cell culture process parameters and downstream processing utilizing a plackett‐burman design for a model monoclonal antibody. (21st November 2016) - Agarabi, Cyrus D.; Chavez, Brittany K.; Lute, Scott C.; Read, Erik K.; Rogstad, Sarah; Awotwe‐Otoo, David; Brown, Matthew R.; Boyne, Michael T.; Brorson, Kurt A.
Abstract : Linkage of upstream cell culture with downstream processing and purification is an aspect of Quality by Design crucial for efficient and consistent production of high quality biopharmaceutical proteins. In a previous Plackett‐Burman screening study of parallel bioreactor cultures we evaluated main effects of 11 process variables, such as agitation, sparge rate, feeding regimens, dissolved oxygen set point, inoculation density, supplement addition, temperature, and pH shifts. In this follow‐up study, we observed linkages between cell culture process parameters and downstream capture chromatography performance and subsequent antibody attributes. In depth analysis of the capture chromatography purification of harvested cell culture fluid yielded significant effects of upstream process parameters on host cell protein abundance and behavior. A variety of methods were used to characterize the antibody both after purification and buffer formulation. This analysis provided insight in to the significant impacts of upstream process parameters on aggregate formation, impurities, and protein structure. This report highlights the utility of linkage studies in identifying how changes in upstream parameters can impact downstream critical quality attributes. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:163–170, 2017